Produção de água e análise econômica na soja irrigada por aspersão convencional no município de Alegrete – RS - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Water has a vital function throughout the cycle of crops, and is a production factor that combined with soil conditions can compromise the results of the grain harvest. The soybean crop stands out in the national economy, and in the state of Rio Grande do Sul the exploration of areas with soybean cultivation has been increasing. Allied to this, the irregularities in rainfall distribution are frequent and the lack of knowledge of water use in the soil and its variables further compromises the productive performance. Thus, the objective of this work was to analyze the economic response of the soy crop irrigated by conventional irrigation. The experiment was conducted in the experimental area of the Instituto Federal Farroupilha - Campus Alegrete, the experimental design used was completely randomized with four treatments with nine repetitions each. The treatments of irrigation were determined with the help of replacement of the evapotranspiration of the crop, the treatments were divided into: Treatment 1 (T1) - 100% of ETc, Treatment 2 (T2) - 70% of ETc, Treatment 3 (T3)- 50% of ETc, and Treatment 4 (T4) - 0% of ETc (testemu-nage). The total water applied was 795.5 mm (T1), 653.93 mm (T2), 606.75 mm (T3) and 418.0 mm (T4). Supplemental irrigation provides an increase in grain yield of soybean, the response of irrigation is linked to the sensitivity of the crop to water deficit, the blade that best corresponds to maximum technical efficiency and productivity of water is the blade with replacement of 70% of ETc.
Keywords: Engenharia agrícola; Irrigação agrícola; Irrigação por aspersores; Soja; Análise econômica; Agricultural engineering; Agricultural irrigation; Sprinkler irrigation; Soy; Economic analysis; CNPQ::CIENCIAS AGRARIAS